Investigation of Luminescence Characteristics of Osmium(II) Complexes in the Presence of Heparin Polyanions. (16th July 2013) - Xie, Yixi; Lei, Yu; Shah, Shalini; Wu, Hao; Wu, Jian; Megehee, Elise; Wang, Enju
Abstract : The luminescence characteristics of six osmium carbonyl complexes with phenanthroline (phen) or bipyridine (bpy) and pyridine (py), 4-phenylpyridine (4-phpy), or triphenylphosphine (PPh3 ) complexes in the presence of polyanion heparin were studied in both ethanol and aqueous solutions. The influence of heparin on the luminescence of the complexes is heavily dependent on the type of ligands in the complexes and the solvent used. In the ethanol solutions, the heparin solution enhanced the luminescence of the five osmium complexes, with the strongest enhancement to the 4-phenylpyridine complexes; linear curves were obtained in the luminescence enhancement ratio (F / F 0 ) versus the heparin concentration range of 1–40  μ g/mL. In aqueous solutions, heparin quenching of the complexes was more significant; a linear quenching curve was obtained with [Os(phen)2 CO(PPh3 )](PF6 )2 in the lower concentration range of 1–12  μ g/mL. The interaction of these complexes with heparin in the solutions is discussed. The complexes are shown to be successful in the fast and sensitive detection of heparin in commercial injectable samples.